Khazanah Lingua The Personality of Manggarai Speech Society: Ecolinguistic Studies - Iku, Priska Filomena; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2019)
This study aims to describe and explain the functions and meanings of lingua unit forms of characters characterized by ideo-socio-biological. Data in this qualitative research is collected by ethnography method, refer to, and capability while to analyze data using an interactive model of Mills and Huberman assisted by distribution method. The results of this study show: the lingual form of kepus found in the stage of pre-planting, planting, and post-planting, namely ekoleksikon and ekowacana; function and meaning implied in the form of lingual rice field environment, ideological meaning: the hope of rice grows well, the hope of rice plants free from pests and disasters, the hope of abundant crops, the hope of surviving while working the fields, and the hope of welfare; sociological functions and meanings: relationships with gods, relationships with ancestors, relationships with the carers of the land, relationships with others, and relations to ulayat lands; and biological functions and meanings.